3D Ordered Porous Hybrid of ZnSe/N‐doped Carbon with Anomalously High Na+ Mobility and Ultrathin Solid Electrolyte Interphase for Sodium‐Ion Batteries. (14th September 2021) - Li, Xueying; Han, Zhiyuan; Yang, Wenhua; Li, Qiang; Li, Hongsen; Xu, Jie; Li, Hongliang; Liu, Bing; Zhao, Haiguang; Li, Shandong; Wang, Xia; Wu, Xing‐Long
Abstract: Transition metal selenides have been widely used in alkali metal ion batteries owing to their high specific capacities and low cost. However, their reaction kinetics and structural stability are usually poor during cycling, along with ambiguous differences in Li/Na/K‐storage behaviors. Herein, it is revealed that ZnSe possesses better Na + ‐diffusion kinetics (including lower diffusion barrier, smaller activation energy, and higher diffusion coefficients) in comparison with Li + and K +, as evidenced by theoretical calculations and electrochemical studies. The architectural designs of ZnSe‐based anode, including nitrogen‐doped carbon (N, C) and 3D ordered hierarchical pores (3DOHP) to form a 3DOHP ZnSe@N, C hybrid combined with regulating solid electrolyte interphase (SEI), significantly enhance Na + reaction kinetics and accommodate volume changes. The resulting 3DOHP ZnSe@N, C electrodes exhibit outstanding rate capability and good cycling stability (241.6 mAh g −1 in sodium‐ion batteries (SIBs) at 10 A g −1 after 800 cycles), originating from improved electrical conductivity and shortened ion diffusion paths, accompanied by ultrathin and stable SEI with less Na2 CO3 /NaF in organic components and boosted Na2 Se adsorption as sodiation. Moreover, the Na‐storage mechanism in 3DOHP ZnSe@N, C hybrid is further revealed by in situ studies. Accordingly, this study provides a new perspective for designing high‐performance electrode materials for SIBs. Abstract : A 3D ordered hierarchical porous ZnSe@N‐doped carbon hybrid with higher Na + diffusion kinetics than Li + and K + is fabricated. Originating from architectural advantages and optimization of electrolytes, the hybrid delivers a low diffusion barrier and activation energy of Na +, accompanied by the formation of ultrathin solid electrolyte interphase to yield a long cycle life even at 10 A g −1 for sodium‐ion batteries.